Robot arm imitating human upper arm: the design and stress analysis / M.S.I.M Sabari and R.L.A. Shauri - Sabari, M.S.I.M.; Shauri, R.L.A. (UiTM Press, 2022)
In previous work, a developed four degree of freedom (DoF) arm failed to move in actual experiment due to the vibration that occurred at the first joint which carries the heaviest payload of the arm. It indicates the importance of analysing robot design before a prototype can be built for real motion. A new robotic arm that was designed to imitate a human upper arm has four joints which rotate around x, y, and z-axis to move its four links to the required posture of the wrist. The work demonstrates the use of a design software to confirms feasibility of the joints for motion and finite element analysis (FEA) to predict the behaviour of the structure when under force. FEA results showed that most of the links have experienced lower stress levels than of the tensile yield strength of alloy steel material which proved the strength of the structure to sustain the applied 15Nm stress test. Hence, with minor adjustments to match with the size of the existing robot hand, the design is ready for fabrication process in the next study.